Using Hemostatic Agents During Orthodontic Bonding: An In Vitro Study - Berat Serdar Akdeniz; Abdullah Alper Oz; Nursel Arici; Onur Demir; Selim Arici (Galenos Yayinevi, 2015)
Objective:The aim of this in vitro study was to compare the effect of a traditional hemostatic agent on the shear bond strength (SBS) of conventional and self-etching bonding systems to find an efficient procedure for orthodontic bonding.Material and Methods:Extracted human premolars (n=108) were divided into 6 equal groups. Conventional light cure primer was used in groups 1, 2, and 3. Acid etching and primer were applied directly in group 1. Enamel surfaces were covered with a Ankaferd Blood Stopper (ABS), which was used as a hemostatic agent in groups 2 and 3. Orthophosphoric acid was applied on ABS-covered enamel in group 2. Before the acid was applied, the enamel surface was cleaned with wet surgical gauze in group 3. A self-etching primer was used in groups 4, 5, and 6. Similar to the first 3 groups, primer was applied on the enamel surface in group 4. Samples were covered with ABS before the primer was applied in groups 4 and 5. The ABS residue was cleaned with gauze before primer application in group 6. The samples were debonded using a universal testing machine. In addition, SBS and residual adhesive were evaluated.Results:Samples contaminated with hemostatic agent and bonded with the self-etching primer without cleaning the hemostatic agent showed significantly lower SBS (p,0.05). Cleaning the ABS on the enamel surfaces increased the bonding strength of self-etching primers. Groups 5 and 6 showed significantly lower ARI scores (p,0.05).Conclusion:Before bonding orthodontic attachments with conventional and light-cure primers, ABS can be safely used. However, using self-etch primers directly on the ABS-applied enamel surface should be avoided. (Turkish J Orthod 2015;28:38- 43)